Will 1,2-dihydro-1,2-azaborine-based drugs resist metabolism by cytochrome P450 compound I? - Pedro J. Silva (PeerJ, 2016)
1,2-dihydro-1,2-azaborine is a structural and electronic analogue of benzene which is able to occupy benzene-binding pockets in T4 lysozyme and has been proposed as suitable arene-mimicking group for biological and pharmaceutical applications. Its applicability in a biological context requires it to be able to resist modification by xenobiotic-degrading enzymes like the P450 cytochromes. Quantum chemical computations described in this work show that 1,2-dihydro-1,2-azaborine is much more prone to modification by these enzymes than benzene, unless steric crowding of the ring prevents it from reaching the active site, or otherwise only allows reaction at the less reactive C4-position. This novel heterocyclic compound is therefore expected to be of limited usefulness as an aryl bioisostere.